Divine madness - Muchamore, Robert (London : Hodder Children's, 2006)
When CHERUB uncovers a link between eco-terrorist group Help Earth and a wealthy religious cult known as The Survivors, James Adams is sent to Australia on an infiltration mission. It's his toughest job so far. The Survivors' outback headquarters are completely isolated, and the cult's brainwashing techniques mean James is under massive pressure to conform. This time he's not just fighting terrorists. He's got to battle to keep control of his own mind. For official purposes, these children do not exist.
Keywords: CHERUB (Imaginary organization) -- Juvenile fiction; Cults -- Australia -- Juvenile fiction; Ecoterrorism -- Juvenile fiction; Espionage -- Juvenile fiction; Children's stories; Spy stories